Facial Skin Quality Improvement After Treatment With CPM‐HA20G: Clinical Experience in Korea - Park, Je‐Young; Youn, ChoonShik; Lee, Chanwoo; Lee, Kyou Chae; Shin, Heawon; Yeom, Kkot Bora; Park, Juhyuk; Jung, Sungkyu; Kim, Joo Ha; Hong, Wonkyu (Journal of cosmetic dermatology, 2025)
ABSTRACT Background Intradermal injection of CPM‐HA20G, a low‐viscoelasticity hyaluronic acid (HA) dermal filler with glycerol, has been shown to be effective for facial rejuvenation in Caucasians, but research in Asians is limited. Aims This study aimed to evaluate the effectiveness and safety of CPM‐HA20G in enhancing facial skin quality in Korean women using a protocol developed by local aesthetic experts. Patients/Methods In this 24‐week prospective, single‐arm, open‐label study, 20 women received CPM‐HA20G injections in the immediate subdermal layer on the anterior cheek (1 mL per side; total 2 mL) in three sessions every 4 weeks. Evaluations included biophysical assessments covering the four emergent perceptual categories (EPCs) for skin quality and subjective assessment using the Global Aesthetic Improvement Scale. Results Significant improvements in skin glow (skin gloss, epidermal hydration), skin firmness (dermal elasticity, dermal hydration), skin surface evenness (average pore volume, pore area, pore density, pore count, maximum pore depth, total pore volume, skin roughness, sebum secretion, and skin depression volume), skin tone evenness (skin color brightness, skin redness), and transepidermal water loss were observed at Week 12 and Week 24 following the first injection with CPM‐HA20G. Most subjects and investigators reported improvements in overall aesthetic appearance with the treatment, with a 100% improvement rating from both groups at Week 12. No serious adverse reactions were observed. Conclusions Our study provides real‐world insights into the effectiveness and safety of CPM‐HA20G in improving facial skin quality in an Asian population, evaluated through both objective and subjective assessments.